An examination of relationship between quality municipal services and citizen satisfaction in Malaysian local council, Batu Pahat in perspective - Kasim, Rozilah; Bello, Muhammad Umar; Martin, David; Abubakar, Muhammad; Umar, Muhammad Akilu (Path of Science, 2017)
This study examines the relationships that exist between quality municipal service and citizen satisfaction. This paper is, therefore, an examination of Relationship between quality Municipal Service and citizen satisfaction in Batu Pahat, Malaysia. It argues that the constitutional mandate of local council in terms of “function performance” has not been translated into reality in many occasions. Hypothesis was postulated for the study. The methodology adopted is quantitative in nature, 100 questionnaires were administered and 89 were retrieved. Systematic random sampling technic was used to retrieve the respondents’ responses. This study applies SPSS statistical tests and AMOS version 23 and Structural Equation Modeling (SEM) software was used for further analysis. The relationship between these two constructs was then evaluated. The findings in this paper are that quality municipal services have direct effect on citizen satisfaction. The paper shows that, on average quality municipal service enhanced citizen satisfaction. The paper has developed valid and reliable constructs that can be used to measure the effect of quality municipal services on citizen satisfaction with municipal council service delivery. Thus, the paper concludes and recommends that municipal council must attempt to overcome the challenges that have by-passed their performance. The study recommends that there is needs for local municipal to strategies to makes the local council more robust for enhancing the lives of inhabitants and to foster good relationship between the management and local people in the study area. The study also gives recommendation to municipal council to strategies on other factors to enhance citizen welfare.